QIBLA DIRECTION WITH THE CONSTELLATION (STUDY OF DETERMINATION OF QIBLA DIRECTION WITH GUBUG PENCENG) - M Ihtirozun Ni'am; Muhammad Fiki Burhanuddin; Nizma Nur Rahmi (Fakultas Syari'ah dan Hukum UIN Walisongo, 2020)
In the ethnography of Javanese society, Gubug penceng is used as a southern constellation. With a declination value of -63º 05’ 57”, the appearance of this gubug penceng is a bit unique, because it can only be observed by observers who are south of the tropic. However, with a magnitude value of 0.77 and a shape that is easy to remember, it makes the gubug becomes a star that is easily visible to the naked eye. The author here will examine the use of the gubug penceng for determining the direction of the Qibla. Previous writers will take into account the azimuth of the Qibla and the azimuth of the acrux star which is the brightest star in the constellation of the thinner, then determine the direction of the Qibla by referring to the difference between the azimuth acrux and the qibla. This research is a field research which is included in qualitative numerical research. The author will compare the results of the Qibla direction from this gubug penceng with the Qibla direction determined with the help of the azimuth of the Sun. The results of this study found that the gubug penceng can be used as a reference to determine the direction of the Qibla. The qibla direction of the measurement results is quite accurate, because the object of aiming is in the form of a central point of the star. The difference between the direction of the Qibla between using the reference hut is not more than 24 minutes, so the results are quite accurate.